The Effectiveness of Hypnotherapy on Arthritis Pain in The Elderly - Ridawati, Indah Dewi; Oktaviani, Eva; Wijaya, Sapondra (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Most of the elderly have arthritis pain. One of the non-pharmacological treatments for arthritis is hypnotherapy. The purpose of this study was to determine the effectiveness of hypnotherapy on the reduction of arthritis pain in Budi Luhur and Budi Mulia Harapan Kita Nurseries and Saturday Studies, Triwikaton Village, South Sumatra Province. This type of research is a quasi-experimental study without control group design. The sample used was a total sampling of 30 people. Arthritis pain was assessed from the results of the pre test and post test. The results of the Wilcoxon signed rank test showed that the initial and late arthritis pain in the group had a significant difference (p = 0,000). Statistically there was effectiveness of hypnotherapy on the reduction of arthritis pain in the elderly.